2000
DOI: 10.1002/1096-9071(200007)61:3<336::aid-jmv9>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

No association of Borna disease virus with psychiatric disorders among patients in Northern Kyushu, Japan

Abstract: There is controversy over the prevalence of Borna disease virus (BDV) antibodies and its RNA in the peripheral blood mononuclear cells (PBMCs) of psychiatric patients, and the contribution of BDV to human psychiatric disorders. We examined 299 plasma and 229 PBMC samples. No plasma samples were positive for BDV-p40, p24 or gp18 antibodies by western blot analysis. The prevalence of BDV RNA in the psychiatric (schizophrenic) patients (1.8%) was not significantly different from that in the healthy volunteers (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Due to no evidence of BDV infection, we could not compare the results of the IFA and rRT-PCR. Including our previous studies,37,38 there have been several studies suggesting a dissociation between BDV and human psychiatric diseases 33,39-42…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Due to no evidence of BDV infection, we could not compare the results of the IFA and rRT-PCR. Including our previous studies,37,38 there have been several studies suggesting a dissociation between BDV and human psychiatric diseases 33,39-42…”
Section: Discussionmentioning
confidence: 88%
“…However, the conflicting results regarding BDV infection cannot be attributed only to geographic factors. It has been reported that BDV is not associated with psychiatric patients in Kyushu island in Japan, a known endemic area of BDV infection 8,42,49. However, there have been two BDV-positive reports in Brazil, which has not been known to be an endemic BDV infection area 23,24.…”
Section: Discussionmentioning
confidence: 96%
“…The difference in seroprevalence between the two studies may be due to different areas and/ or different patient population. Another recent report revealed that all plasma samples derived from 89 psychiatric patients and 210 healthy volunteers in a western area of Japan were negative for BDV p40, p24, and gp 18 antibodies by WB analysis without an inhibition test, while BDV RNA was detected in 1 to 2% of the patients (47). The difference in seroprevalence may be due to different conditions of the WB assay.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in prevalence could be due to the use of different assay systems (immunofluorescence [IF] assay [4,5,37,38], Western blot [WB] analysis [8,14,15,21,23,24,40,47,50], enzyme-linked immunosorbent assay [14,20,24], and electrochemiluminescence immunoassay [ECLIA] [53]) with different sensitivities and specificities. Particularly, in most of the previous reports that examined BDV antibodies by WB analysis, the specificity for BDV has not been considered, giving rise to the possibility of false-positive results.…”
mentioning
confidence: 99%
“…199 False-positive results in highly capable laboratories have led to incorrect conclusions about infectious agents causing many chronic diseases, including multiple sclerosis and schizophrenia. 142,200,201 Guidelines for establishing causation on the basis of molecular detection techniques are evolving. 202 The findings to date regarding detection of measles virus from studies of intestinal tissue specimens do not meet several of these guidelines.…”
Section: Is Measles Virus Present In the Intestinal Wall In Patients mentioning
confidence: 99%